Bedside Ultrasound of Quadriceps to Predict Rehospitalization and Functional Decline in Hospitalized Elders - Guerreiro, Ana Clara; Tonelli, Ana Claudia; Orzechowski, Roman; Dalla Corte, Roberta Rigo; Moriguchi, Emilio Hideyuki; Mello, Renato Bandeira de (Frontiers in Medicine, 2017)
Objective: To evaluate the capacity of total thigh thickness, quadriceps muscle thickness and quadriceps contractile index, all measured by bedside ultrasound, to predict rehospitalization, functional decline and death in elderly patients 3 months after hospital discharge. To evaluate intra-observer and inter-observer reproducibility of the dominant thigh evaluation method by point of care ultrasound. Methods: Cohort study of patients aged 65 years or more admitted to a medium complexity unit in a teaching hospital in southern Brazil. Comprehensive geriatric assessment and ultrasound evaluation of the dominant thigh of each participant were performed. After three months of hospital discharge, telephone contact was made to evaluate the outcomes of rehospitalization or death and functional decline - assessed by the 100 points Barthel scale and defined as a decrease of 5 or more points. Results: 100 participants were included. There was no statistically significant difference between intra-observer measurements (p>0.05) and the mean bias obtained in Blant-Altman plots was close to zero in all four analyses performed, suggesting good intra and inter-observer agreement. There was a good intra-observer and inter-observer agreement for all tested ultrasound measurements. There was a significat correlation between the echographic measurements (quadriceps thickness and contractile index) and gait speed, timed up and go and handgrip tests. There was a significant association between contractile index (quadriceps thickness over total anterior thigh thickness multiplied by 100) lower than 60% and functional decline (relative risk 1.35; CI95% 1.10-1.65; p=0.02) as well as between the thickness of the quadriceps and rehospitalization or death, in both individuals with preserved walking capacity and in bedridden elders (Relative risk 1.97, 95% CI 1.0-3.95, p = 0.040). Conclusion: the ultrasonographic method to evaluate thigh thickness was easily applicable and reproducible. The thickness of the quadriceps could predict rehospitalization or death, even in those patients without walking capacity - unable to perform gait speed and timed up and go tests. Additionally, the contractile index was associated with functional decline after 3 months of hospital discharge. This is a promising result, which highlights bedside ultrasound of the quadriceps as a potential tool for the prognosis evaluation of bedridden hospitalized elderly patients.